Plasmodium knowlesi malaria during pregnancy - Barber, Bridget E. (2015)
Background: Plasmodium knowlesi is the commonest cause of malaria in Malaysia, but little is known regarding infection during pregnancy. Methods: To investigate comparative risk and consequences of knowlesi malaria during pregnancy, we reviewed (1) Sabah Health Department malaria-notification records created during 2012–2013, (2) prospectively collected data from all females with polymerase chain reaction (PCR)–confirmed malaria who were admitted to a Sabah tertiary care referral hospital during 2011–2014, and (3) malaria microscopy and clinical data recorded at a Sabah tertiary care women and children's hospital during 2010–2014. Results: During 2012–2013, 774 females with microscopy-diagnosed malaria were notified, including 252 (33%), 172 (20%), 333 (43%), and 17 (2%) with Plasmodium falciparum infection, Plasmodium vivax infection, Plasmodium malariae/Plasmodium knowlesi infection, and mixed infection, respectively. Among females aged 15–45 years, pregnancy was reported in 18 of 124 (14.5%), 9 of 93 (9.7%), and 4 of 151 (2.6%) P. falciparum, P. vivax, and P. malariae/P. knowlesi notifications respectively (P = .002). Three females with knowlesi malaria were confirmed as pregnant: 2 had moderate anemia, and 1 delivered a preterm low-birth-weight infant. There were 17, 7, and 0 pregnant women with falciparum, vivax, and knowlesi malaria, respectively, identified from the 2 referral hospitals. Conclusions: Although P. knowlesi is the commonest malaria species among females in Sabah, P. knowlesi infection is relatively rare during pregnancy. It may however be associated with adverse maternal and pregnancy outcomes.